Z igro glasov v angleškem jeziku do razvijanja fonološkega zavedanja - Čok, Lucija; Brčaninović, Anita (Revija za elementarno izobraževanje, 2015)
From Playing With Sounds in English to the Development of Phonological Awareness. For the last few decades we have witnessed an increased interest in introducing foreign languages at early stages of education. The introduction of a foreign language at pre-school level may occur in an integrated manner or in the form of additional activities which is also reflected in the pre-school curriculum. However, in both cases, special attention should be given to the development of listening skills, especially to phonological awareness. This paper presents a model for developing phonological awareness skills in learning English as a foreign language which can be adapted for different types of pre-school programmes and other foreign languages. The implementation of the outlined activities may facilitate children’s literacy development both in their first and foreign language.